Ultra-thin polyethylene oxide solid electrolyte film and preparation method thereof
By using polymer-supported substrate and hydrogen bond crosslinking technology in solid electrolyte films, the contradiction between thickness and mechanical strength is solved, the preparation of ultra-thin solid electrolyte films is realized, and its ionic conductivity and mechanical properties are improved. in supercapacitors and batteries.
Patent Information
- Application Number
- CN202210372914.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-08
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-04-08
AI Technical Summary
In the prior art, there is a contradiction between minimizing thickness and maintaining mechanical strength, and it is difficult to achieve effective reduction of thickness and increase of ionic conductivity.
Polyoxyethylene solid electrolyte films modified with polymer support substrate and crosslinking are prepared by hydrogen bond crosslinking technology and multiple rolling processes to prepare a uniform film of 5-30μm, and the insulated porous polymer supports the substrate and hydrogen. The bond crosslinking agent forms a networked structure to improve mechanical properties and ion transmission efficiency.
It realizes precise regulation of the mechanical properties and thickness of ultra-thin solid electrolyte films, improves the ionic conductivity of solid electrolytes and the safety of devices, and is suitable for supercapacitors and batteries.
Smart Images

Figure CN114613615B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid electrolytes, and in particular relates to an ultra-thin polyethylene oxide solid electrolyte film and a preparation method thereof. Background Art
[0002] Solid electrolytes are also called fast ion conductors. They can be roughly divided into inorganic solid electrolytes, polymer solid electrolytes and composite solid electrolytes according to their components. Polymer solid electrolytes are composed of polar polymers and metal salts, which are similar to the components of organic liquid electrolytes. Compared with organic liquid electrolytes, polymer solid electrolytes have the advantages of excellent safety, excellent thermal stability, a wider electrochemical window (slightly higher than organic liquid electrolytes), good flexibility and processability.
[0003] Most of the current research on all-solid-state polymer electrolytes focuses on enhancing ionic conductivity and improving interface stability, while the thickness of the electrolyte membrane has received less attention.
[0004] Jingyi Wu, Lixia Yuan, Wuxing Zhang, Zhen Li, Xiaolin Xie and Yunhui Huang, "Reducing the thickness of solid-state electrolyte membranes for high-energy lithium batteries". Energy Environ. Sci., 2021, 14, 12-36.
[0005] The paper points out that the internal resistance of the battery depends on the ionic conductivity and charge transfer impedance of the solid electrolyte, among which the ionic conductivity (G = σA / L, G is ionic conductivity, σ is ionic conductivity, A is area, and L is thickness) is inversely proportional to the thickness of the electrolyte. The main reason is that reducing the thickness shortens the transmission time of ions in the electrolyte. Therefore, preparing ultra-thin solid electrolyte films can improve their ionic conductivity.
[0006] The difficulty in designing ultrathin solid electrolyte films lies in the contradiction between minimizing thickness and maintaining mechanical strength. Summary of the invention
[0007] The purpose of the present invention is to overcome the deficiencies in the prior art and to provide an ultra-thin polyethylene oxide solid electrolyte film and a preparation method thereof.
[0008] This ultra-thin polyethylene oxide solid electrolyte film includes: a polymer support substrate and a cross-linked polyethylene oxide solid electrolyte matrix, the polymer support substrate is located between two layers of cross-linked polyethylene oxide solid electrolyte matrix; the polymer support substrate is a polymer film, and the cross-linking modification method of the polyethylene oxide solid electrolyte matrix is hydrogen bond cross-linking.
[0009] Preferably, the polymer support substrate is an insulating porous material with a thickness of 5 to 10 μm, and the thickness of the polyethylene oxide solid electrolyte matrix 2 is 5 to 15 μm.
[0010] Preferably, the polymer support substrate is made of at least one of polytetrafluoroethylene, polyvinylidene fluoride and polyimide.
[0011] Preferably, the overall thickness of the ultra-thin polyethylene oxide solid electrolyte film is 5 to 30 μm.
[0012] Preferably, the cross-linked modified polyethylene oxide solid electrolyte matrix is a solid electrolyte matrix formed by complexing polyethylene oxide and an electrolyte salt.
[0013] Preferably, the molar ratio of the crosslinking agent hydrogen bond donor to the polyethylene oxide hydrogen bond acceptor in the polyethylene oxide solid electrolyte matrix is 1:1 to 1:10.
[0014] The method for preparing the ultra-thin polyethylene oxide solid electrolyte film comprises the following steps:
[0015] Step 1, dispersing polyethylene oxide and electrolyte salt in acetonitrile according to a set molar ratio, and stirring until completely dissolved;
[0016] Step 2, adding a crosslinking agent and polyethylene oxide to the solution obtained in step 1 according to a set molar ratio of the hydrogen bond acceptor, stirring until completely dispersed, to obtain a dispersion;
[0017] Step 3, dripping the dispersion obtained in step 2 on both sides of the polymer support substrate respectively, coating the dispersion evenly, drying to remove the solvent, and obtaining a thin film on both sides of the polymer support substrate;
[0018] Step 4: Place the film-polymer support substrate-film structure obtained in step 3 in a roller press, and roll it multiple times at rolling gaps from large to small to obtain an ultra-thin polyethylene oxide solid electrolyte film with uniform thickness, wherein the pores in the polymer support substrate of the ultra-thin polyethylene oxide solid electrolyte film are filled with polyethylene oxide solid electrolyte; the symbol - indicates a composite connection.
[0019] Preferably, in step 2, the cross-linking agent provides at least two hydrogen bond donors, and the hydrogen bond donors simultaneously undergo hydrogen bond cross-linking with multiple polyethylene oxide chains; the specific hydrogen bond cross-linking method is: the hydrogen bond donors provided by the cross-linking agent form hydrogen bonds with the ether oxygen in the polyethylene oxide to form a network structure, thereby improving the mechanical properties of the solid electrolyte film; the cross-linking agent includes urea, thiourea and trihydroxymethylphenol.
[0020] Preferably, in step 1, the molar ratio of polyethylene oxide to the electrolyte salt is 1:8 to 1:20; in step 2, the molar ratio of the crosslinking agent to the hydrogen bond acceptor in polyethylene oxide is 1:1 to 1:10; in step 3, after the dispersion is evenly coated, it is dried at 60° C. for 12 hours to remove the solvent.
[0021] Preferably, in step 3, the coating height of the dispersion when coating both sides of the polymer support substrate is 100 to 500 μm.
[0022] The beneficial effects of the present invention are:
[0023] The solid electrolyte film proposed in the present invention is a film composed of a polymer support substrate and a cross-linked modified polyethylene oxide solid electrolyte, and is a uniform solid electrolyte film of 5 to 30 μm obtained after multiple rolling; the polymer support substrate is a polymer film, and the cross-linking modification is hydrogen bond cross-linking.
[0024] The insulating porous polymer support substrate not only serves as the supporting skeleton of the solid electrolyte film, but also ensures ion transmission and electronic insulation. Polyethylene oxide contains ether oxygen non-shared electron pairs and has a strong affinity for hydrogen bonds. The present invention uses a cross-linking agent with multiple hydrogen bond donors. Multiple hydrogen donors of the cross-linking agent simultaneously form hydrogen bonds with different polyethylene oxide chains. Different polyethylene oxide chains are interconnected through the cross-linking agent to achieve a network structure, thereby improving the mechanical properties of the solid electrolyte. The present invention can reduce the deformation of the film caused by rolling by rolling the solid electrolyte film multiple times, and obtain a uniform solid electrolyte film of 5 to 30 μm.
[0025] The present invention can achieve precise control of the mechanical properties and thickness of the solid electrolyte film by controlling the molar ratio of the crosslinking agent / polyethylene oxide and the roller pressing distance. For the difficulty in designing ultra-thin solid electrolyte films, the present invention provides a feasible design idea, and has the advantages of being simple and economical, and can be used in supercapacitors and batteries to improve the safety of the devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the structure of an ultra-thin polyethylene oxide solid electrolyte film;
[0027] Figure 2 This is a step profiler scan of an ultra-thin polyethylene oxide solid electrolyte film;
[0028] Figure 3 The electrochemical performance diagram of the solid-state supercapacitor based on ultrathin polyethylene oxide solid electrolyte film;
[0029] Figure 4 The step analyzer scans of ultra-thin polyethylene oxide solid electrolyte films of different thicknesses;
[0030] Figure 5 This is a graph showing the tensile properties of different polyethylene oxide solid electrolyte films.
[0031] Description of the reference numerals: polymer support substrate 1, cross-linked modified polyethylene oxide solid electrolyte matrix 2. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with embodiments. The description of the following embodiments is only used to help understand the present invention. It should be noted that for ordinary persons in the art, without departing from the principle of the present invention, the present invention can also be modified in some ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0033] Example 1
[0034] like Figure 1 As shown, an ultra-thin polyethylene oxide solid electrolyte film comprises: a polymer support substrate 1 and a cross-linked polyethylene oxide solid electrolyte matrix 2, wherein the polymer support substrate 1 is located between two layers of cross-linked polyethylene oxide solid electrolyte matrix 2; the polymer support substrate 1 is a polymer film, and the cross-linking modification method of the polyethylene oxide solid electrolyte matrix is hydrogen bond cross-linking.
[0035] The polymer support substrate 1 has a thickness of 5 to 10 μm, and the material of the polymer support substrate 1 is at least one of polytetrafluoroethylene, polyvinylidene fluoride and polyimide. The overall thickness of the ultra-thin polyethylene oxide-based solid electrolyte film is 5 to 30 μm.
[0036] The cross-linked modified polyethylene oxide solid electrolyte matrix 2 is a solid electrolyte matrix formed by complexing polyethylene oxide and electrolyte salt. The molar ratio of the cross-linking agent hydrogen bond donor to the polyethylene oxide hydrogen bond acceptor in the polyethylene oxide solid electrolyte matrix is 1:1 to 1:10.
[0037] Example 2
[0038] Preparation of ultra-thin polyethylene oxide solid electrolyte film and performance test of solid supercapacitor, the specific steps are as follows:
[0039] (1) Weigh a certain weight of polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide at a lithium-oxygen ratio of 1:8, dissolve them in a certain volume of acetonitrile solvent, and stir them magnetically for 24 hours until they are completely dissolved;
[0040] (2) adding urea to the above solution at a molar ratio of urea to polyethylene oxide of 1 / 10, and stirring magnetically for 12 h until completely dissolved to obtain a dispersion;
[0041] (3) taking a 10 μm thick polytetrafluoroethylene (PTFE) film as a supporting substrate, and dropping a certain volume of the dispersion obtained in step 2 on both sides of the PTFE film;
[0042] (4) Using a coater with a thickness of 100 μm, apply the dispersion solution dropped in step 3, and allow the coated sample to dry naturally;
[0043] (5) rolling the sample obtained in step (4) three times in sequence at three rolling intervals from large to small to obtain an ultra-thin polyethylene oxide solid electrolyte film;
[0044] The sample with a thickness of 5.5 μm obtained in step 5 of this embodiment was scanned using a Bruker Dektak XT-A step profiler, and the following Figure 2 The step profiler scan of the ultra-thin polyethylene oxide solid electrolyte film shown.
[0045] Using activated carbon as the electrode, the charge and discharge cycle test was carried out at 50°C with a current density of 0.1 mA / mg and a voltage range of 0 to 2.5 V. The test results are as follows: Figure 3 As shown: After 50 cycles, the capacity retention rate can reach 94%, and the charge and discharge efficiency remains at 90%.
[0046] Example 3
[0047] Ultra-thin polyethylene oxide solid electrolyte films of different thicknesses are prepared as follows:
[0048] (1) Weigh a certain weight of polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide at a lithium-oxygen ratio of 1:15, dissolve them in a certain volume of acetonitrile solvent, and stir them magnetically for 24 hours until they are completely dissolved;
[0049] (2) According to the molar ratio of urea to polyethylene oxide being 1 / 20, urea was weighed into the above solution and magnetically stirred for 12 h until it was completely dissolved;
[0050] (3) taking a polytetrafluoroethylene (PTFE) film with a thickness of 10 μm as a supporting substrate, and dropping a certain volume of the dispersion prepared in step 2 on both sides of the PTFE film;
[0051] (4) Using a coater with a thickness of 100 μm, apply the dispersion solution dropped in step 3, and allow the coated sample to dry naturally;
[0052] (5) For the samples in step 4, rolling was performed four times at rolling intervals of 18-16-11-11, 18-16-16-16, and 18-18-18-18, respectively, to obtain three samples of different thicknesses, which were rolled three times in sequence. The equipment used was a Bruker DektakXT-A step profiler to test the sample thickness.
[0053] Figure 4 These are the step analyzer scans of ultra-thin polyethylene oxide solid electrolyte films of different thicknesses. The measured sample thicknesses are 5.6μm, 16.5μm, and 25.6μm, respectively.
[0054] Example 4
[0055] Comparing the tensile properties of polyethylene oxide solid electrolyte, the preparation process is as follows:
[0056] (1) Weigh a certain weight of polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide at a lithium-oxygen ratio of 1:15, dissolve in a certain volume of acetonitrile solvent, and stir magnetically for 24 hours until completely dissolved. Repeat the steps to prepare two solutions;
[0057] (2) Urea was weighed into the solution at a molar ratio of urea to polyethylene oxide of 1 / 10, and magnetically stirred for 12 h until it was completely dissolved. This solution was numbered solution 1. The solution without urea was numbered solution 2.
[0058] (3) 15 ml of solution 1 and solution 2 were added to a PTFE box respectively and dried naturally to obtain film 1 (containing urea) and film 2 (without urea);
[0059] (4) Cut film 1 / 2 into a rectangular shape of 1*2 cm, and compare the tensile properties of film 1 and film 2.
[0060] Figure 5 The tensile properties of different polyethylene oxide solid electrolyte films are shown in Figure 1. The maximum force elongation of film 1 is 60%, while that of film 2 is only 19%. The tensile properties of film 1 are better than those of film 2.
Claims
1. An ultra-thin polyethylene oxide solid electrolyte film, It is characterized in that include: A polymer support substrate (1) and a cross-linked modified polyethylene oxide solid electrolyte matrix (2), wherein the polymer support substrate (1) is located between two layers of cross-linked modified polyethylene oxide solid electrolyte matrix (2); The polymer support substrate (1) is a polymer film, and the cross-linking modification method of the polyoxyethylene solid electrolyte matrix is hydrogen bond cross-linking; the preparation method of the ultra-thin polyoxyethylene solid electrolyte film comprises: Step 1, dispersing polyethylene oxide and electrolyte salt in acetonitrile according to a set molar ratio, and stirring until completely dissolved; Step 2, adding a crosslinking agent and polyethylene oxide to the solution obtained in step 1 according to a set molar ratio of the hydrogen bond acceptor, stirring until completely dispersed, to obtain a dispersion; In step 2, the cross-linking agent provides at least two hydrogen bond donors, and the hydrogen bond donors simultaneously form hydrogen bond cross-links with multiple polyethylene oxide chains; the specific hydrogen bond cross-linking method is: the hydrogen bond donors provided by the cross-linking agent form hydrogen bonds with the ether oxygen in the polyethylene oxide to form a network structure; the cross-linking agent includes urea, thiourea and trihydroxymethylphenol; Step 3, dripping the dispersion obtained in step 2 on both sides of the polymer support substrate respectively, coating the dispersion evenly, drying to remove the solvent, and obtaining a thin film on both sides of the polymer support substrate; Step 4: Place the film-polymer support substrate-film structure obtained in step 3 in a roller press, and roll it multiple times at rolling gaps from large to small to obtain an ultra-thin polyethylene oxide solid electrolyte film with uniform thickness; the symbol - indicates a composite connection.
2. The ultra-thin polyethylene oxide solid electrolyte film according to claim 1, Features: The polymer support substrate (1) is an insulating porous material with a thickness of 5 to 10 μm, and the thickness of the polyethylene oxide solid electrolyte matrix (2) is 5 to 15 μm.
3. The ultra-thin polyethylene oxide solid electrolyte film according to claim 2, Features: The material of the polymer support substrate (1) is at least one of polytetrafluoroethylene, polyvinylidene fluoride and polyimide.
4. The ultra-thin polyethylene oxide solid electrolyte film according to claim 1, Features: The overall thickness of the ultra-thin polyethylene oxide solid electrolyte film is 5 to 30 μm.
5. The ultra-thin polyethylene oxide solid electrolyte film according to claim 1, Features: The cross-linked modified polyethylene oxide solid electrolyte matrix (2) is a solid electrolyte matrix formed by complexing polyethylene oxide and an electrolyte salt.
6. The ultra-thin polyethylene oxide solid electrolyte film according to claim 1, Features: The molar ratio of the crosslinking agent hydrogen bond donor to the polyethylene oxide hydrogen bond acceptor in the polyethylene oxide solid electrolyte matrix is 1:1 to 1:
10.
7. The ultra-thin polyethylene oxide solid electrolyte film according to claim 1, Features: In step 1, the molar ratio of polyethylene oxide to the electrolyte salt is 1:8 to 1:20; in step 2, the molar ratio of the crosslinking agent to the hydrogen bond acceptor in polyethylene oxide is 1:1 to 1:10; in step 3, after the dispersion is evenly coated, it is dried at 60° C. for 12 h to remove the solvent.
8. The ultra-thin polyethylene oxide solid electrolyte film according to claim 1, Features: In step 3, the coating height of the dispersion when coating both sides of the polymer support substrate is 100 to 500 μm.
Citation Information
Patent Citations
Multifunctional composite film for chemical power source
CN103950239A
Composite diaphragm for battery and preparation method thereof
CN104103791A
Solid electrolyte with polymer micro-particles implanted in situ and preparation method thereof
CN107768729A
Manufacturing method of high-depth-to-width-ratio and high-load miniature supercapacitor
CN110233064A
Preparation method of ionic conductor / polyoxyethylene composite solid electrolyte based on ultraviolet crosslinking
CN111313089A
